The Role of Servant Leadership in Enhancing Hospital Performance: Examining the Mediating Effect of Employee Engagement and Organizational Culture - Barin Barlian; Suryana Suryana; Disman Disman; Budi Santoso (Dinasti International Journal of Education Management and Social Science, 2026)
This study comprehensively analyses hospital performance that is directly or indirectly influenced by servant leadership through the mediation of employee engagement and organisational culture, taking into account the supporting role of contemporary healthcare organisational dynamics.  This study used a quantitative approach with a cross-sectional survey design. This study used a quantitative cross-sectional survey design the ability to draw causal conclusions, as it does not allow for observation of changes in variables over time. The study participants consisted of 385 health workers working in various service units (nurses, doctors, and administrative staff) from six hospitals in Indonesia. Hypothesis testing used Structural Equation Modeling (SEM) with AMOS software to analyze the direct and indirect relationships between servant leadership, employee engagement, organizational culture, and hospital performance. This study showed that servant leadership has a positive and significant effect on hospital performance. In addition, servant leadership also has a positive and significant effect on employee engagement and organizational culture. Furthermore, the results confirm that employee engagement and organizational culture partially mediate the relationship between servant leadership and hospital performance. This study contributes to filling the empirical evidence gap in developing health systems, particularly regarding collective mediation mechanisms in the relationship between leadership and organizational performance. These findings have important implications for hospital management to adopt and implement servant leadership principles optimally to improve organisational performance. Hospital leaders should encourage managers and unit heads to apply a leadership style that is oriented towards service, empowerment, and employee development.